Quinny & Hopper - Schanen, Adriana Brad; Swearingen, Greg 1976- (Los Angeles : Disney/Hyperion Books, 2014)
"Two polar-opposite eight year olds who become summer best friends find their friendship threatened by the uncertainties of a new school year"--
Keywords: Best friends -- Juvenile fiction; Friendships -- Juvenile fiction; Individuality -- Juvenile fiction; Peer pressure -- Juvenile fiction; Schools -- Juvenile fiction; Neighbors -- Juvenile fiction; Humorous Stories; Best friends -- Fiction; Friendships -- Fiction; Individuality -- Fiction; Peer pressure -- Fiction; Schools -- Fiction; Neighbors -- Fiction; Humorous Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / School & Education